2018
DOI: 10.3390/toxins10020082
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Improve the Clinical Utility of Saporin-Based Targeted Toxins

Abstract: Plant Ribosome-inactivating proteins (RIPs) including the type I RIP Saporin have been used for the construction of Immunotoxins (ITxs) obtained via chemical conjugation of the toxic domain to whole antibodies or by generating genetic fusions to antibody fragments/targeting domains able to direct the chimeric toxin against a desired sub-population of cancer cells. The high enzymatic activity, stability and resistance to conjugation procedures and especially the possibility to express recombinant fusions in yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 123 publications
(160 reference statements)
1
60
0
Order By: Relevance
“…Saporin is a ribosome‐inactivating protein found in the seeds of the plant Saponaria officinalis . It functions as an rRNA N ‐glycosylase that inhibits protein synthesis by cleaving a specific adenine base from ribosomal RNA (28S), irreversibly damaging the ribosomes . We found that administering MC‐813‐70 and saporin as an immunotoxin complex gave rise to a significant reduction in the viability of SSEA‐4‐expressing MDA‐MB‐231 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Saporin is a ribosome‐inactivating protein found in the seeds of the plant Saponaria officinalis . It functions as an rRNA N ‐glycosylase that inhibits protein synthesis by cleaving a specific adenine base from ribosomal RNA (28S), irreversibly damaging the ribosomes . We found that administering MC‐813‐70 and saporin as an immunotoxin complex gave rise to a significant reduction in the viability of SSEA‐4‐expressing MDA‐MB‐231 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Saporin is approximately 30kd molecular weight. It does not have a natural cell binding domain, so it is active only when it is endocytosed with a receptor-specific molecule or similar mechanism and transferred into the cytosol [11]. e type I RIP is a very powerful toxin in cancer therapy, and the major problem with its use is the need to combine it with some means to transfer it from the endosome to the cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…This study addressed the effectiveness of Saporin, Chlorotoxin and CTX-SAP conjugate in decreasing cell viability of ML-1 cells. Saporin, a toxin from the plant seed Saponaria officinalis , inhibits proliferation or cell viability of cancer cells (23). Previous studies have proven that Saporin is an effective ribosome-inactivating protein (RIP) that inhibits protein synthesis and growth of both normal and tumor cells (24).…”
Section: Discussionmentioning
confidence: 99%